2000
DOI: 10.1021/np000176e
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxic Constituents of Polyalthia longifolia var. pendula

Abstract: A new halimane diterpene, 3beta,5beta, 16alpha-trihydroxyhalima-13(14)-en-15,16-olide (1), and a new oxoprotoberberine alkaloid, (-)-8-oxopolyalthiaine (2), along with 20 known compounds, were isolated from a methanolic extract of Polyalthia longifolia var. pendula. The structures of compounds 1 and 2 were established by spectroscopic analysis. Several of these compounds were evaluated for cytotoxicity toward a small panel of human cell lines.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
71
0
1

Year Published

2003
2003
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 100 publications
(73 citation statements)
references
References 32 publications
1
71
0
1
Order By: Relevance
“…Moreover, the bark is also used to treat bone fracture, gastric ulcer, and digestive and urinary disorders (Moniruzzaman et al, 2015). , extracted from the bark of p. longifolia, exhibits strong anti-inflammatory activity (Chang et al, 2006;Chen et al, 2000), regulates the expression of histone modifying enzymes PRC2 complex, and induces apoptosis in CML K562 cells (Lin et al, 2011). Many natural compounds and certain chemotherapeutic drugs are shown to trigger caspase-independent autophagic cell death by activating autophagy signaling pathways (Kondo et al, 2005;Xu et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the bark is also used to treat bone fracture, gastric ulcer, and digestive and urinary disorders (Moniruzzaman et al, 2015). , extracted from the bark of p. longifolia, exhibits strong anti-inflammatory activity (Chang et al, 2006;Chen et al, 2000), regulates the expression of histone modifying enzymes PRC2 complex, and induces apoptosis in CML K562 cells (Lin et al, 2011). Many natural compounds and certain chemotherapeutic drugs are shown to trigger caspase-independent autophagic cell death by activating autophagy signaling pathways (Kondo et al, 2005;Xu et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…longifolia var. pendula has been less investigated compared with P. longifolia (Chen et al, 2000;Hara et al, 1995). Recent studies on its stem, roots, root bark and their isolates showed excellent antibacterial potency (Faizi et al, 2000(Faizi et al, , 2003a(Faizi et al, , 2003b) and significant hypotensive activity (Faizi et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…It is used as an antipyretic agent in indigenous systems of medicine (Khatoon, 1985). Biological evaluation of the plant has resulted in the isolation of diterpenes and alkaloids which have been reported to be cytotoxic against human cancer cell lines (Chen et al, 2000) and to possess antimicrobial (Ferdous et al, 1992;Rashid et al, 1996) activity. Recently, a lactone with promising antibacterial activity has been isolated from the stem (Faizi et al, 2003).…”
Section: Introductionmentioning
confidence: 99%